Atlas of common bean production in Africa. (2nd ed.) - Farrow, Andrew; Muthoni Andriatsitohaina, Rachel (Pan-Africa Bean Research Alliance, 2020)
The Atlas of Common Bean (Phaseolus vulgaris L.) Production in Africa, second edition, is a revision of the previous atlas published in 1998 (Wortmann et al., 1998). This revised edition is updated with additional information and addresses more topics. The data and indicators in the 1998 version were structured in seven main themes: environment of bean production areas, socio-economic characterisation, bean cropping systems, distribution of bean seed types, bean diseases, bean pests, and abiotic constraints. The data collection was a rich mix of compiled secondary data and expert knowledge, with further research carried out in a decentralised manner by teams in each country, with support from the Pan-Africa Bean Research Alliance (PABRA). Since 1998, agriculture in Africa has grown into new frontiers, increased demand for beans has resulted in intensification of production, and crop management options have reduced losses resulting from pest and disease infestation. Some African farmers are also responding to bean export opportunities due to increased production surpluses. Nevertheless, there is much variation across bean production areas in Africa, especially regarding opportunities and obstacles in increasing bean production and improving marketing access. Compiling, mapping, monitoring, and interpreting information on these differences led to the production of this second edition of the Atlas of Common Bean (Phaseolus vulgaris L.) Production in Africa.